Exploring Early Childhood Development Interventions for Building Human Capital in Sub‐Saharan Africa: A Scoping Review. - Beukes, Johanna; Alcock, Stephanie; Leal, Michelle; Thompson, Urlridge; Draper, Catherine E.; Norris, Shane A. (Child: Care, Health & Development, 2025)
Background: Inequalities in the provision and implementation of early childhood development (ECD) interventions in Sub‐Saharan Africa remain a challenge. This scoping review aimed to investigate the types and extent of ECD interventions in this region, using the Nurturing Care framework (NCF). Methods: This review included randomised controlled trial (RCT) studies related to ECD interventions in Sub‐Saharan Africa. Sources from 2019 to 2024 were included. PubMed, MEDLINE (Ebsco), Web of Science, ProQuest and PsychInfo were searched in September 2024. Abstracts and full texts were reviewed using Rayyan. Results: Of 85 studies retrieved, 21 conducted across 13 countries were included in our review. Most were conducted in Eastern and Southern Africa, with Western and Central Africa notably underrepresented. Sample sizes varied from 134 to over 9000 participants. ECD interventions targeting children from 0 to 8 years old were included. Nutrition‐focused interventions were the most common (n = 9) and showed the biggest positive impact on child weight and growth. Responsive caring interventions were the second most common (n = 2), resulting in fewer reports of maltreatment, reduced endorsement of corporal punishment and fewer behavioural problems in children. The remaining three NCF dimensions (i.e., early learning opportunities, safety and security, and good health) each had only one intervention focusing solely on that dimension and showed mixed results on child development. Multidimensional interventions were common, with seven studies combining multiple ECD support elements to create a holistic approach. Although these interventions showed mixed results, they were more likely to report positive outcomes across multiple NCF domains compared to single‐focus interventions. Conclusions: Most interventions focus only on a couple of NCF elements. There is a need for increased focus on underrepresented regions to address local ECD needs effectively and to develop and evaluate interventions that incorporate all elements of NCF in African contexts. Summary: Nutrition‐focused ECD interventions are most prevalent in the Sub‐Saharan African context, whereas most fail to integrate all five Nurturing Care Framework (NCF) components, limiting their potential developmental impact.Despite evidence supporting responsive caregiving and early learning for long‐term child development, these domains remain severely underrepresented in ECD interventions in Sub‐Saharan Africa.Interventions incorporating more than one NCF domain reported mixed results, with limited reported effectiveness attributed to short durations, implementation challenges and contextual barriers.Sub‐Saharan African ECD research is heavily concentrated in Eastern and Southern Africa, whereas Western and Central Africa remain underrepresented, highlighting a need for geographically inclusive research.Future ECD research must prioritise longitudinal studies, multisectoral approaches and locally tailored interventions that address structural barriers and contextual realities, especially in low‐resource settings.